Voltammetric Properties of Nickel Hexacyanoferrate (III) Obtained on the Titanium (IV) Silsesquioxane Occluded into the H-FAU Zeolite for Detection of Sulfite - Do Carmo, Devaney Ribeiro [UNESP]; Maraldi, Vitor Alexandre [UNESP]; Cumba, Loanda Raquel [UNESP] (My University, 2018)
A composite prepared from titanium (IV) silsesquioxane and phosphoric acid (TTiP) was prepared and occluded into the H-FAU zeolite (ZTTiP). The material was chemically modified with nickel and subsequently by potassium hexacyanoferrate (III) (ZTTiPNiH). It was preliminarily characterized by infrared spectroscopy (IR), energy dispersive X-ray spectroscopy (EDS) and cyclic voltammetry (CV). The voltammetric behavior of ZTTipNiH was obtained employing a modified graphite paste electrode (GPE) showing one well-defined redox couple with a formal potential of E(Formula presented.) 0.51V (vs Ag/AgCl(sat)), KCl (3M) (20% w/w; v = 20 mV s− 1; KCl; 1.00 mol L− 1) corresponding to the NiIIFeII(CN)6/NiIIFeIII(CN)6 redox process. After rigorous voltammetric studies, the GPE modified with ZTTiPNiH was applied for facile and rapid detection of sulfite. From the analytical curve, a linear response was obtained in a concentration range of 0.05 to 0.80 mmol L− 1 and a detection limit (3σ) of 0.05 mmol L− 1 with a relative standard deviation of 4.21% (n = 3) and an amperometric sensitivity of 14.42 mA L mol− 1 for sulfite.
Keywords: Nickel hexacyanoferrate (III); Silsesquioxanes; Sulfite; Titanium (IV) silsesquioxane; Voltammetry; Zeolite